Association between Comorbidities and Progression of Transvalvular Pressure Gradients in Patients with Moderate and Severe Aortic Valve Stenosis. (11th November 2018) - Salinger, Tim; Hu, Kai; Liu, Dan; Taleh, Scharoch; Herrmann, Sebastian; Oder, Daniel; Gensler, Daniel; Müntze, Jonas; Ertl, Georg; Lorenz, Kristina; Frantz, Stefan; Weidemann, Frank; et al.
Abstract : Background . Fast progression of the transaortic mean gradient ( P mean ) is relevant for clinical decision making of valve replacement in patients with moderate and severe aortic stenosis (AS) patients. However, there is currently little knowledge regarding the determinants affecting progression of transvalvular gradient in AS patients. Methods . This monocentric retrospective study included consecutive patients presenting with at least two transthoracic echocardiography examinations covering a time interval of one year or more between April 2006 and February 2016 and diagnosed as moderate or severe aortic stenosis at the final echocardiographic examination. Laboratory parameters, medication, and prevalence of eight known cardiac comorbidities and risk factors (hypertension, diabetes, coronary heart disease, peripheral artery occlusive disease, cerebrovascular disease, renal dysfunction, body mass index ≥30 Kg/m 2, and history of smoking) were analyzed. Patients were divided into slow ( P mean < 5 mmHg/year) or fast ( P mean ≥ 5 mmHg/year) progression groups. Results . A total of 402 patients (mean age 78 ± 9.4 years, 58% males) were included in the study. Mean follow-up duration was 3.4 ± 1.9 years. The average number of cardiac comorbidities and risk factors was 3.1 ± 1.6. Average number of cardiac comorbidities and risk factors was higher in patients in slow progression group than in fast progression group (3.3 ± 1.5 vs 2.9 ± 1.7;P = 0.036 ). Patients in slow progression group had more often coronary heart disease (49.2% vs 33.6%;P = 0.003 ) compared to patients in fast progression group. LDL-cholesterol values were lower in the slow progression group (100 ± 32.6 mg/dl vs 110.8 ± 36.6 mg/dl;P = 0.005 ). Conclusion . These findings suggest that disease progression of aortic valve stenosis is faster in patients with fewer cardiac comorbidities and risk factors, especially if they do not have coronary heart disease. Further prospective studies are warranted to investigate the outcome of patients with slow versus fast progression of transvalvular gradient with regards to comorbidities and risk factors.